Technological Dimensions of Nearly ZEB Design: Evolving toward a Nearly Zero Energy Oriented Landscape - Angelucci, Filippo (Journal of Technology Innovations in Renewable Energy, 2018)
Today, the implementation framework of Zero Energy Building strategies is characterised by a complex transitional phase. In fact, it is still difficult to achieve completely autonomous buildings, disconnected from any power-supply network. Despite the negative impact of climate-change and the progressive loss of non-renewable resources on our lifestyles, the global economic-financial crisis, local cultural-technological barriers, and the cost/complexity of design processes keep investment in this area unattractive. However, there is an intermediate approach that can facilitate a gradual re-direction of building actions through the ZEB logic. It can be identified in the alternative of Near Zero Energy Building (Nearly ZEB or Near Net ZEB). The Nearly ZEB approach, with its multiplicity of design aspects (i.e. cognitive, analytical, technical, and managerial) may configure a widespread state of progressive transition towards the architectural/inhabitable constructions sought by the 20-20-20 logic, at the scale of the building, the city, and the landscape. These constructions have lower emissions, produce more energy from renewable sources, consume less non-renewable energy, and can â€œalsoâ€ reach the objective of total energy autonomy (ZEB) or Plus Energy. A twofold operating scenario emerges from this point of view. It is centred on the technological dimensions of designing a Nearly Zero Energy living space by overcoming the traditional concept of a building as a single object. On the one hand, there is a need for a greater interaction between technological innovations and inhabitable spaces, in a trans-scalar key; design becomes an open process of technological-environmental modifications that addresses the transition towards the status of ZEB. On the another hand, it becomes fundamental that the relationship between interior and exterior space, both public and private, is increasingly focused on the design of interface-systems in order to harmonise three new levels of relations (city-building, city-land, and building-land) and to configure a Nearly Zero Energy Oriented Landscape. These aspects emerge from the contributions presented in this special issue on The Technological Dimensions of Nearly Zero Energy Building Design and will be addressed in this essay.